Effects of a Selective D⁴ Antagonist on Repetitive Behaviors in a Genetic Model of ADHD in Rats - Parks, Lina (My University, 2022)
This study aimed to investigate the efficacy of the selective D4 antagonist, A-412997, on repetitive behaviors of a rodent model of ADHD. We hypothesized that the drug would have no significant effect on repetitive behavior compared to the control groups. This would indicate that the D4 antagonist is comparable to and more effective than other treatments of ADHD, such as methylphenidate. Our study found significant strain effects for all three behaviors (digging, inactivity, and marble interaction) between the Long Evens control group and the spontaneously hypertensive rat (SHR) experiment group. We found that there were no significant impacts of drug exposure on marble interaction time and bouts, time spent inactive, bouts inactive, or digging time. Overall, this indicated that A-412997 could be an effective treatment for ADHD when looking at the possible side effects. Future directions should investigate other possible repetitive behaviors, in order to be sure that there is no confounding behavior that is impacted by this drug.